Development of Contextual Physics Module inspired by Banyuwangi Local Wisdom for Senior High School - Linda Ali Ramadani; Albertus Djoko Lesmono; Yushardi Yushardi (Bulletin of Social Studies and Community Development, 2022)
Abstract: Describe and produce modules based on local wisdom as valid and practical for teaching materials Senior High School. Using Nieveen's research design consisting of preliminary research, prototyping stage,  and assessment stage. Preliminary research begins by analyzing the needs of problem analysis and literature studies as a basis for making modules. Prototyping stage is done by expert validation and user validation before the module is taught. In assessment stage, valid modules were tested in class XI MIPA 2 to measure the practicality of the module. Practicality of modules based on learning implementation and student response questionnaire sheets of 95.3% and 91.6%. The contextual physics module based on the local wisdom of Banyuwangi developed is valid and practical so that it is worthy of use.   Keywords: local wisdom, practicality, physics modules, validity